The Problematics of Welfare State Practices and the Construction of Justice in the Operationalization of BPJS Health - Mayrudin, Yeby Ma'asan; Amal, Mohamad Ilyasul (Journal of Social and Policy Issues, 2025)
This article aims to explain the phenomena that occur when providing unfair services in the field of BPJS Health services; and understand the concept of a welfare state and social justice in providing BPJS Health services. The welfare state is still a crucial issue for every country. Public welfare is still questioned by the public regarding state administration. Thus, the issue of welfare and justice in the implementation of BPJS health with assistance from key informant for the meaning of justice and prosperity. The article uses the theory of Jeremy Bentham which examines concepts welfare state with a focus on welfare and happiness from the government. Using qualitative research methods with a phenomenological approach from Cresswell which focuses on the meaning of justice and welfare based on experiences key informant BPJS users. The results of this research are BPJS has entered the concept welfare state but the facts on the ground speak differently, people are still competing to achieve prosperity and happiness in Indonesia. The facts answer that: First, there is still discrimination in people's access to health. Second, the lack of equality in obtaining the right to health. Third, the community does not have the right to health. Fourth Many people get happiness through nepotism.